COMMUNITY EMPOWERMENT BASED ON LOCAL ECONOMIC POTENTIAL AT KUBE KALIGONDANG PURBALINGGA VILLAGE - Amanah Aida Qur'an (Ilmu Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Unsoed, 2023)
The emergence of the idea of community empowerment through the Joint Business Group (KUBE) approach is based on the idea that everyone has potential and abilities that can be developed. However, the awareness and participation of KUBE members in the sustainability of the program is very low. Islam wants social change to eradicate injustice and improve people's welfare.This type of research is field research with a case study approach. The data analysis technique used is descriptive qualitative by using interview, observation and documentation techniques as data collection tools. Primary data sources were obtained from the Purbalingga District Social Service, TKSK (District Social Worker) Kaligondang, assistants and members of KUBE Kaligondang. Meanwhile, secondary data was obtained from books on empowerment, previous research discussing empowerment in KUBE and data from the internet.The conclusion is that community empowerment in KUBE is still at the level of manipulation where the community is involved in a program, but in fact their involvement is not based on a mental, psychological drive, and is accompanied by the consequences of participation that contributes to the program.